2011
DOI: 10.1080/10382046.2011.619807
|View full text |Cite
|
Sign up to set email alerts
|

Development of an online hazards atlas to improve disaster awareness

Abstract: Understanding the causes, effects and geographic patterns of local hazards is important for helping individuals make educated decisions about how to respond to their threat. Unfortunately, it is often difficult to find comprehensive sources of information about local hazards. In this paper, we discuss the development of an online hazards atlas for the state of South Carolina. We have designed this atlas to facilitate awareness about the causes and effects of hazards. An effective method for communicating this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…"These issues are the basis for an education oriented towards the future" (Reinfried, 2004, p. 249). Battersby, Mitchell, and Cutter (2011) later reinforced this view by recognising that hazards can be useful in capturing student attention. This is important when educating about how to reduce the impact of disasters.…”
Section: Editorialmentioning
confidence: 96%
See 1 more Smart Citation
“…"These issues are the basis for an education oriented towards the future" (Reinfried, 2004, p. 249). Battersby, Mitchell, and Cutter (2011) later reinforced this view by recognising that hazards can be useful in capturing student attention. This is important when educating about how to reduce the impact of disasters.…”
Section: Editorialmentioning
confidence: 96%
“…Blanchard-Boehm and Cook (2004) have indicated that in order to motivate hazard preparedness and mitigation, we need resources that can communicate clearly to individuals with little to no personal experience with specific hazards. Battersby et al (2011) also contributed to the notion that educational materials designed to improve public awareness are needed so that the public make more intelligent decisions about preparation, survival and recovery. Mitchell, Borden, and Schmidtlein (2008) and Mitchell (2009) reminded us, that in terms of hazards, "student's understanding would be best fostered by using an approach equally [considering] natural and human processes" (Mitchell et al, 2008, p. 183-184), and that "why we should teach about them is … fairly straightforward.…”
Section: Editorialmentioning
confidence: 99%
“…Although they recognized the usefulness of identifying the most vulnerable areas, stakeholders also wanted to see what made these places vulnerable. According to Battersby, Mitchell, and Cutter (2011), Web sites enriched by maps are an appropriate means to provide information about vulnerability, but since expert judgement and local knowledge about vulnerability often deviate, the importance of including local knowledge in vulnerability assessments needs to be recognized (Naess and others 2006). We therefore find that the first point above represents a sound scepticism regarding our topdown expert assessment of vulnerability.…”
Section: Identifying Stakeholders' Needsmentioning
confidence: 99%
“…Several studies emphasize that there is a need to improve public awareness so that individuals can make more intelligent decisions about preparing for surviving and recovering from hazards when they occur (Battersby et al 2011). Also, a finding in previous studies shows that preparation is positively affected by personal concerns about the hazard (Green et al 1981).…”
mentioning
confidence: 92%